Kepuasan kerja di kalangan guru teknikal di Sekolah Menengah Teknik: satu kajian kes di Daerah Rompin, Pahang Darul Makmur - Mohd. Yusof, Bin Hj. Hassan (1997)
This is an initial study to identify the level of job satisfaction among teachers Sekolah Menengah Teknik (SMT) in the district of Rompin, Pahang Darul Makmur. The study was intended to determined factors influencing job satisfaction among the teachers. Satisfaction on the teacher's present responsibilities, income, promotion prospects, work supervision, co-workers and the job itself in general were evaluated. Seventy-two teachers were involved in the study.